The role of software Modellus in a teaching approach based on model analysis - Soares, Débora da Silva; Borba, Marcelo C. [UNESP] (Springer Nature, 2014)
We discuss some results of a study carried out over the past 4 years to investigate the role of Modellus, a software package, in the development of an approach to teaching calculus for Biology majors. The central idea of the teaching approach is to propose the analysis of a mathematical model for a biological phenomenon at the very beginning of the course, in a way that this analysis is interrelated with some of the mathematical concepts listed in the syllabus. In this paper, we focus on the role of the software during the development of one of the activities proposed to the students, the purpose of which was to discuss the relation between secant lines and the instantaneous rate of change. It was found that this software played two roles in the development of this activity: providing information about the phenomenon and the model; and acting as a trigger, making evident to the student an important aspect that contributed to his understanding. Based on our theoretical perspective of digital technology, we believe that students’ interaction with the software played a fundamental role in the thinking collective composed of humans and media involved in mathematical learning.
Keywords: Digital technology; Mathematical modeling; Mathematics education